2018
DOI: 10.1108/jima-11-2014-0076
|View full text |Cite
|
Sign up to set email alerts
|

Islamic symbols in food packaging and purchase intention of Muslim consumers

Abstract: Purpose Purchase intention of consumers depends on their perception of the extent to which his expectations will be met through the product. This issue, in the context of the products that are immediately purchased by consumer, depends on the extent of relationship in the point of sale. Packaging is one of the most significant factors influencing purchase decision in the point of sale. In this research, the purpose is evaluating the impact of using Islamic symbols in food packaging on the purchase intention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…As highlighted by Biswas and Roy (2015) and Lin and Huang (2012), novelty-seeking not only serves to fulfil the preservation instinct, which may be beneficial in creating a useful knowledge database, but can also improve problem-solving skills, which affects an individual's consumption of products. Moreover, it has been found that customers are more inclined to choose halal-certified products that are marketed effectively, for instance, when healthier ingredients, better packaging and more extensive product information are provided (Akbari et al, 2018;Bonne et al, 2007). Past studies have also demonstrated that consumers are more likely to search for facts and information on the production process prior to making a purchase (Biswas and Roy, 2015;Mohd Suki, 2016), particularly in the selection of halal-certified food supplies because some customers were found to seek information on the product ingredients as well as on the certification process of the relevant bodies (Talib et al, 2015).…”
Section: Epistemic Valuementioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by Biswas and Roy (2015) and Lin and Huang (2012), novelty-seeking not only serves to fulfil the preservation instinct, which may be beneficial in creating a useful knowledge database, but can also improve problem-solving skills, which affects an individual's consumption of products. Moreover, it has been found that customers are more inclined to choose halal-certified products that are marketed effectively, for instance, when healthier ingredients, better packaging and more extensive product information are provided (Akbari et al, 2018;Bonne et al, 2007). Past studies have also demonstrated that consumers are more likely to search for facts and information on the production process prior to making a purchase (Biswas and Roy, 2015;Mohd Suki, 2016), particularly in the selection of halal-certified food supplies because some customers were found to seek information on the product ingredients as well as on the certification process of the relevant bodies (Talib et al, 2015).…”
Section: Epistemic Valuementioning
confidence: 99%
“…This then further emphasizes the importance of consumer perception as one of the salient factors in determining consumer purchasing behaviour (Chen et al, 2009). Therefore, taking the literature on the significance of religious values in influencing consumer behaviour towards the purchase of halal-certified products (Ahmed et al, 2019;Akbari et al, 2018;Arsil et al, 2018) into consideration, the following hypothesis was developed: H3. The concern about halal certification significantly influences Muslim customer's choice behaviour towards halal-certified food supplies.…”
Section: Halal Concernmentioning
confidence: 99%
“…(2010) explored that consumer's use of product information source is influenced by religiosity. Religiosity also performs the role of moderating variable; for example, the relationship between environmental orientation and marketing practices, and the relationship between ego‐defensive advertisement and customer attitudes is moderated by religiosity (Adi & Adawiyah, 2018; Akbari et al., 2018; Ariffin et al., 2016; Wahyuni & Fitriani, 2017). Religiosity also performs mediating role (Mansour & Diab, 2016; Yeniaras, 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Many marketers appear to assume that religious symbols in advertising create strong meanings in a religious society (Taylor et al , 2010). Such an assumption has led to a growing scholarly interest in how religion such as Islam is influencing consumer behaviour (Akbari et al , 2018).…”
Section: Religion and Advertisingmentioning
confidence: 99%